The Cerebellum: From Development to Learning - Jose A. Armengol; Salvador Martinez (Frontiers Media SA, 2015)
In this book, laboratory leaders on cerebellar neuroscience have revised the present body of knowledge about cerebellum anatomy and function. The trip throughout the cerebellar vineyard organization starts from the causal study of morphogenesis (that is, the molecular and cellular mechanisms underplaying form generation) to the molecular mechanism regulation cellular differentiation: Basson, Dusart, Hawkes, Martinez and Rosi$1 (Bs groups contributions. Then, neurodevelopmental anomalies associated with structural disorganization are revised in Jissendi and Batkovich$1 (Bs group reviews, describing and discussing pathogenic processes. Finally, functional mechanisms of cerebellar circuits involved in motor learning are revised by Delgado-Garcia and Armengol$1 (Bs group contribution.s
English
Keywords: motor learning; Cerebellar genoarchitecture; Cerebellar malformation; Cerebellar histogenesis; cerebellum development